2007
DOI: 10.1179/174329306x147544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nd:YAG laser + pulsed MAG arc hybrid welding parameters on its weld shape

Abstract: Weld penetration depth, width, reinforcement and reinforcement to width ratio were defined as the factors to evaluate the weld shape. The effects of Nd:YAG laserzpulsed metal active gas (MAG) arc hybrid welding parameters on the weld shape were investigated with bead on plate tests. The results indicated that the laser energy mainly decides the weld penetration and the weld width depends on the arc for a given welding speed. The Nd:YAG laser has some effects on the hybrid weld appearance in varying of laser-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…(19) and (20), as given below, for gas temperature, K T , and density, K The thermodynamic state and velocity of the air on each side of the shock wave are related by the Rankine-Hugoniot relations, where the most convenient forms to this application are given by Eqs. (21) and (22). K M is the Mach number in the vapor, /2…”
Section: Laser-induced Recoil Pressure and Keyhole Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…(19) and (20), as given below, for gas temperature, K T , and density, K The thermodynamic state and velocity of the air on each side of the shock wave are related by the Rankine-Hugoniot relations, where the most convenient forms to this application are given by Eqs. (21) and (22). K M is the Mach number in the vapor, /2…”
Section: Laser-induced Recoil Pressure and Keyhole Dynamicsmentioning
confidence: 99%
“…1, hybrid laser-arc welding is formed by combining laser beam welding and arc welding. Due to the synergic action of laser beam and welding arc, hybrid welding offers many advantages over laser welding and arc welding alone [3][4][5][6] , such as high welding speed, deep penetration 7 , improved weld quality with reduced susceptibility to pores and cracks [8][9][10][11][12][13][14][15][16] , excellent gap bridging ability [17][18][19][20][21][22] , as well as good process stability and efficiency, as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…The weld width (L u , L l ), the fusion zone area (A (A = A u + A s + A l ), A s ), the reinforcement height (H u , H l ), and the reinforcement height-to-width ratio (r u , r l ) were used to evaluate the weld shape. A smaller reinforcement height-to-width ratio means a better spreadability of the filler metal [17]. The average laser power (P) and the peak power (Pp) are defined as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al (2006) observed the hybrid laser-MIG welding phenomenon in butt joints with different gap conditions by using a high speed camera. Qin et al (2007) experimentally investigated the effects of Nd:YAG laser and pulsed MAG arc hybrid welding parameters on the weld shape. The obtained results indicated that the laser energy would affect the weld penetration and the weld width would depend on the arc parameters for a given welding speed.…”
Section: Introductionmentioning
confidence: 99%